Rational Inattention, Competitive Supply, and Psychometrics. Issue 3 (13th April 2020) - Caplin, Andrew; Csaba, Dániel; Leahy, John; Nov, Oded
Abstract: We introduce a simple method of recovering attention costs from choice data. Our method rests on a precise analogy with production theory. Costs of attention determine consumer demand and consumer welfare, just as a competitive firm's technology determines its supply curve and profits. We implement our recovery method experimentally, outline applications, and link our work to the broader literature on inattention and mistaken decisions.